Technoeconomics and lifecycle assessment of bioreactors : Wastewater treatment plant management - Andalib, Tarnima Warda; Zaied, Khalid; Mishra, Puranjan
This chapter discusses the fundamental concepts of techno-economics and the ways that impact the bioreactors especially discusses the challenges of wastewater treatment scenarios. This chapter reveals the relationship between various techno-economic networks with bioreactors. The techno-economic assessment generally analyses and examines the technology development against the necessary economic variables like costs, benefits, uncertainties, timeframes, etc., to measure and estimate the effects of the innovative technology. The extended segment is named as a techno-economic paradigm as well. Therefore, here the fundamental concepts are discussed along with their impact on the bioreactors especially while dealing with the wastewater treatment plant approach.